PENGEMBANGAN PERMAINAN KARTU KATA DALAM MENINGKATKAN KEMAMPUAN MEMBACA PADA ANAK USIA DINI - Fu’ad Arif Noor; Yuliningsih (QURROTI, 2021)
This study is to find out how the implementation of word card games in improving early childhood reading in BA 'Aisyiyah Pugeran Karangdowo Klaten. This study uses a class action type, the subject is group B BA 'Aisyiyah Pugeran Karangdowo Klaten, totaling 29, consisting of 14 male students and 15 female students. Data collection techniques used are interviews, observation, and documentation. While the research instruments used were interview guidelines and observation sheets. The results of this study indicate that: the implementation of the word card game is carried out in several steps, namely: a) the teacher asks questions about the names of the letters and shows them with the existing letter cards; b) explain the purpose and rules of the game; c) prepare children to line up waiting for their turn, d) children line up in the yard, e) the teacher puts letter cards on the floor at random both vowels and consonants at an arranged distance, f) children jump on vowels and after arriving at the end the child is asked to take one of the letters and mention the sound of the letter he took and put it back in the container based on the group, namely vowels or consonants, g) cooling activities. The increase in reading ability in early childhood after using word card media which was originally 34.48% increased in the first cycle to 51.72% and in the second cycle it reached 82.76%. So the increase in children's reading skills at BA 'Aisyiyah Pugeran after the implementation of this word card game was 48.28%.